2022
DOI: 10.1002/dys.1729
|View full text |Cite
|
Sign up to set email alerts
|

Growing up with dyslexia: Child and parent perspectives on school struggles, self‐esteem, and mental health

Abstract: Children with dyslexia, compared with typically reading peers, are at increased risk of internalising (e.g., anxiety) and externalising (e.g., aggression) mental health concerns; why this is the case is largely unknown. Our aim was to explore the socio‐emotional experience of growing up with dyslexia from both child and parent perspectives. In so doing, we aimed to gain a better understanding of self‐esteem and mental health in the context of dyslexia. One‐to‐one semi‐structured interviews with 17 children wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 50 publications
(80 reference statements)
0
26
0
2
Order By: Relevance
“…In contrast, some mothers reported having excellent relationships with their children's school based on frequent and open communication and their concerns/recommendations listened to and acted upon. From our analysis, this sense of school connectedness (feeling included, supported and respected at school; Libbey, 2004) was an important protective factor for both mothers' and children's well‐being (see also, Wilmot et al, in press). For example, Karen had moved her son to a new school that focused on “not just academic” but also “emotional well‐being.” She expressed how she could relax her watch a little, trusting her child's new school, because she felt listened to and valued, which lessened her worry:
I've just relaxed, still get worried but he'll get there, he'll get, we'll all get there [] the school, their communications are a lot better than where we were previously and the reassurance as well cos I did also say, “I hope I'm not coming across as annoying by asking 50 million questions all the time” but he said “oh no that's what our job is, if you're happy then the kids are happy.”
…”
Section: Discussionmentioning
confidence: 75%
See 1 more Smart Citation
“…In contrast, some mothers reported having excellent relationships with their children's school based on frequent and open communication and their concerns/recommendations listened to and acted upon. From our analysis, this sense of school connectedness (feeling included, supported and respected at school; Libbey, 2004) was an important protective factor for both mothers' and children's well‐being (see also, Wilmot et al, in press). For example, Karen had moved her son to a new school that focused on “not just academic” but also “emotional well‐being.” She expressed how she could relax her watch a little, trusting her child's new school, because she felt listened to and valued, which lessened her worry:
I've just relaxed, still get worried but he'll get there, he'll get, we'll all get there [] the school, their communications are a lot better than where we were previously and the reassurance as well cos I did also say, “I hope I'm not coming across as annoying by asking 50 million questions all the time” but he said “oh no that's what our job is, if you're happy then the kids are happy.”
…”
Section: Discussionmentioning
confidence: 75%
“…Our analysis took a neurodiversity perspective and was guided by Braun and Clarke's reflexive thematic analysis approach (2006, 2013, 2022). This article is a companion piece to another, which focused on children's mental health in the context of dyslexia and included both child and parent perspectives (Wilmot et al, in press).…”
Section: Concluding Commentsmentioning
confidence: 99%
“…Rather, a large body of literature focuses on genetics and neurodevelopmental impairments of at‐risk children of parents with dyslexia (Chan & Mo, 2023; Denton et al, 2022; Earey, 2013; Leitao et al, 2017; Skinner, 2011), and another growing area on parents' (i.e. mostly mothers) concerns about the educational experience of their children with dyslexia (Aberz, 2022; Wilmot et al, 2022). An exception is research by Skinner (2011) and Skinner and MacGill (2015), who explored the intersection of how mothering and work is affected among women with dyslexia.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies verified the child's diagnosis by the child's diagnostic report (Levi, 2017;Moore, 2021;Paisner-Roffman, 2018;Porter et al, 2020;Washburn, 2014), and others relied on parents' understanding of the study's inclusion/exclusion criteria and their child's diagnoses. Three studies included the child's experience of living with dyslexia, alongside the parent's experience (Kelley, 2022;Leitao et al, 2017;Moore, 2021;Wilmot et al, 2022). Several studies also collected data from teachers or school administrators as part of the study (Kelley, 2022;Mahoney, 2020;Paisner-Roffman, 2018).…”
Section: Sampling Characteristicsmentioning
confidence: 99%
“…Many parents reported that their concerns were not taken seriously when raised with their child's school. Studies captured the experience of parent concerns being dismissed/parents told 'not to worry' (Kelley, 2022;Levi, 2017;Mahoney, 2020;Miesch, 2020;Moore et al, 2017;Owens, 2021;Wilmot et al, 2022;Wilmot et al, 2023;Woodcock, 2020), and parents told to just 'wait and see' or that their child just needs more time (Kelley, 2022;Miesch, 2020;Owens, 2021). In addition, parents reported that child difficulties were being misattributed as poor behaviour and motivation or due to poor parenting (Chien & Lee, 2013;DeBrew, 2017;Moore, 2021;Silverstein, 2015).…”
Section: Barriers and Facilitators To Timely Diagnosismentioning
confidence: 99%